2020
DOI: 10.1021/acschemneuro.0c00232
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Conjugates of Silybin as Prodrugs for Targeting Toxic Aβ Aggregates

Abstract: Alzheimer's disease (AD) is linked to the abnormal accumulation of amyloid β peptide (Aβ) aggregates in the brain. Silybin B, a natural compound extracted from milk thistle (Silybum marianum), has been shown to significantly inhibit Aβ aggregation in vitro and to exert neuroprotective properties in vivo. However, further explorations of silybin B's clinical potential are currently limited by three main factors: (a) poor solubility, (b) instability in blood serum, and (c) only partial knowledge of silybin's mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Unfortunately, the authors did not consider transport over the hemato-encephalitic barrier, which would be presumably impermeable for such a big molecule. The above findings prompted the group of García-Viñuales et al [102] to prepare other C-23 conjugates of silybin A and B with trehalose linked via a phosphate diester bond (Figure 8) by coupling reactions between the respective silybin-23-phosphoramidite and the appropriately protected trehalose, catalyzed by 4,5-dicyanoimidazole. Here again, a better activity in terms of inhibiting the aggregation of amyloid β peptide was found in the respective silybin B derivative.…”
Section: Pharmacokinetics Of Silybin With Regard To Its Stereochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the authors did not consider transport over the hemato-encephalitic barrier, which would be presumably impermeable for such a big molecule. The above findings prompted the group of García-Viñuales et al [102] to prepare other C-23 conjugates of silybin A and B with trehalose linked via a phosphate diester bond (Figure 8) by coupling reactions between the respective silybin-23-phosphoramidite and the appropriately protected trehalose, catalyzed by 4,5-dicyanoimidazole. Here again, a better activity in terms of inhibiting the aggregation of amyloid β peptide was found in the respective silybin B derivative.…”
Section: Pharmacokinetics Of Silybin With Regard To Its Stereochemistrymentioning
confidence: 99%
“…Recent studies have shown that conjugation of a trehalose moiety to silybin A and B (Figure 8) increases water solubility without significantly affecting anti-aggregation properties [102]. An NMR study showed that silybins may act by shielding toxic Aβ40 surfaces formed by N-terminal and CHC-Aβ regions, and that the aromatic ring A of silybin is the primary site for interaction with Aβ-oligomers.…”
Section: Neurological Activitymentioning
confidence: 99%
“…However, Aβ40 is more abundant than Aβ42 (9:1) in the biological fluids (Qiu et al, 2015). In addition, Aβ40 was found in the amyloid deposits of patients affected by cerebral amyloid pathology, which is considered an early step in AD pathogenesis (Garcia-Vinuales et al, 2020;Greenberg et al, 2020), suggesting that both isoforms must be taken in consideration in search of neuroprotective agents.…”
Section: Natural Compounds With Inhibitory Effects On Aβ Peptide Aggrmentioning
confidence: 99%
“…Chemical modifications have been successfully introduced in curcumin to remove labile moieties and improve the water solubility in physiological conditions, preserving the ability to bind Aβ oligomers and plaques (Airoldi et al, 2011). The chemical conjugation of the active natural compounds with a prodrug moiety that do not inactivate its inhibitory properties and effectively improve the molecule pharmacokinetic is a promising strategy applied for quercetin (Guzzi et al, 2017) and silybin (Garcia-Vinuales et al, 2020). In particular, glycoconjugation of silybin with trehalose resulted in a significant increase of the bioavailabity, with improved solubility and half-life in blood serum.…”
Section: Ability Of Inhibitors To Cross Blood Brain Barrier and Stratmentioning
confidence: 99%
See 1 more Smart Citation